Index Catchment-A Tool For Water Balance Study in The Arid Zone of India - Vangani, N S; Chatterji, P C (Annals of Arid Zone, 2016)
A considerable area of western Rajasthan is composed of impeded drainage basins bounded by the dune ridges and eroded rocky outcrops. Method for computing groundwater balance of impeded basins as independent hydrological unit have been termed as Index Catchments. The results obtained from three different methods of water balance computation of two index catchments in the Nagaur district and that of the district area, were statistically analysed and were found to be of same order. It has been suggested to adopt the 'Index Catchment's a method of water balance studies for minimal time and manpower requirements.